Periodontal disease and its impact on general health in Latin America. Section V: Treatment of periodontitis - Fischer,Ricardo Guimarães (2020)
Abstract: Gingivitis and periodontitis are associated with a negative impact on Oral Health Related Quality of Life (OHRQoL), exerting a significant influence on aspects related to the patients' function and esthetics. Periodontitis has been associated with several systemic conditions, including adverse pregnancy outcomes, cardiovascular diseases, type 2 diabetes mellitus (DM), respiratory disorders, fatal pneumonia in hemodialysis patients, chronic renal disease and metabolic syndrome. The aim of this paper was to review the results of different periodontal treatments and their impacts on patients' OHRQoL and systemic health. Non-surgical and surgical periodontal treatments are predictable procedures in terms of controlling infection, reducing probing pocket depth and gaining clinical attachment. In addition, the treatment of periodontitis may significantly improve OHRQoL and promote a reduction in the levels of systemic markers of inflammation, including some cytokines associated with cardiovascular diseases. Studies have also suggested that periodontal treatment may improve glycemic control in patients with DM. Strategies and actions for preventing the onset and recurrence of periodontitis, and the challenges facing the field of periodontology in the XXI century are presented in this review.